Developing Applications for Children With Special Needs Into a Project Based Learning Approach at Human-Computer Interaction Course - Ilijoski, Bojan; Ackovska, Nevena (IEEE, 2022)
Caring for the vulnerable categories of people is particularly important for the development of societies. Especially when it comes to children with special needs, who should be offered a variety of opportunities for education and integration. We try to help in the creation of digital tools by integrating project development for these target groups within the subject of human-computer interaction. This approach has several benefits for all parties involved. Students learn new technologies, and develop a complete product, while getting acquainted with the problems that children with special needs have. In this way, in addition to the technical knowledge, they also get satisfaction from the work they do to help the society. As end users, the children and their parents receive a wide range of tools they can use in education or in everyday functioning.
Keywords: application development , children with special needs , project based learning , human - computer interaction course